Vulvovaginal fibroepithelial stromal polyp with myxoid stroma: A diagnostic dilemma on histology - Report of two cases - Urvashi Ghosh; Debahuti Mohapatra; Nibedita Sahoo (Wolters Kluwer Medknow Publications, 2020)
Genital stromal tumors are a rare and unique subset of soft-tissue tumors encountered in the vulvovaginal and inguinoscrotal region and this group includes fibroepithelial stromal polyp, superficial (cervicovaginal) myofibroblastoma, cellular angiofibroma, mammary-type myofibroblastoma, angiomyofibroblastoma, superficial angiomyxoma, and deep/aggressive angiomyxoma. The relative rarity and overlapping histomorphological and immunohistochemical features result in a diagnostic difficulty for the pathologists. Herein, we describe two cases of soft-tissue tumors in the vulvovaginal region presenting as polypoidal mass with detailed histopathology and immunohistochemical workup.